The Effect of Long-Term Proton Pump Inhibitor Use on Frailty Syndrome in Elderly Patients - Stephanie Dewi; Purwita W Laksmi; Ari Fahrial Syam; Esthika Dewiasty; Euphemia Seto (Jurnal Penyakit Dalam Indonesia)
Introduction. Frailty syndrome, the newest elderly health predictor, associated with higher morbidity and mortality. PPI are often used in elderly due to presence of upper gastrointestinal complaints, and relates with polypharmacy as one of the risk factor for frailty syndrome. There is no study of the relationship between long term PPI use and frailty syndrome in elderly.